Jugo de caña de azúcar envasado en vidrío - Aguirre, M. (2011)
This product has been develop in order to offer to the population one kind of refresh and delicious bottled liquid using high manufacture practices (BPM), innovation and quality control in all the process used. The research and development to the transformation of this product, the sugar cane juice was transformed using sugar cane from the Amazonia jungle, special variety (Limeña) it is because your quality and flavor is special for this purpose. The steps used to transform the sugar cane was cut, washer, extraction , filter,clarifite and bottling, during the process was made chemicals and physicals analysis, microbiological, sensorial , all this examinations give like the results following dates soluble solids 16.3 °Brix ,PH 3.76;total coli forms <3 UFC/ml; misfiles aero bios, <1.0 UFC/ml ,levaduras and moods <1.0 UFC/ml and fecal coli forms <3 UFC/ml ; uniform color ,natural flavor and excellent characteristics with qualities to use without restrictions to the populations. The results certify using the norms like BPM and INEN with all the recommendations and in the future can get the certification like a GREEN PRODUCT with high value